2003
DOI: 10.1046/j.1365-294x.2003.01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mosaic in a marine species flock

Abstract: We used molecular approaches to study the status of speciation in coral reef fishes known as hamlets (Serranidae: Hypoplectrus). Several hamlet morphospecies coexist on Caribbean reefs, and mate assortatively with respect to their strikingly distinct colour patterns. We provide evidence that, genetically, the hamlets display characteristics common in species flocks on land and in freshwaters. Substitutions within two mitochondrial DNA (mtDNA) protein-coding genes place hamlets within a monophyletic group relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 70 publications
5
82
0
1
Order By: Relevance
“…Hamlets Hypoplectrus spp. exhibit distinct color morphs and are known to mate assortatively (Puebla et al 2007), although mitochondrially, Hypoplectrus are unresolved and suggestive of recent speciation (McCartney et al 2003, Ramon et al 2003. If observed patterning differences observed in O. aurifrons do serve as mate recognition characters, then it is probable that polymorphisms in genes controlling patterning are driving phenotypic differences, even though mitochondrial loci were incompletely sorted (Palumbi et al 2001, Avise 2004.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamlets Hypoplectrus spp. exhibit distinct color morphs and are known to mate assortatively (Puebla et al 2007), although mitochondrially, Hypoplectrus are unresolved and suggestive of recent speciation (McCartney et al 2003, Ramon et al 2003. If observed patterning differences observed in O. aurifrons do serve as mate recognition characters, then it is probable that polymorphisms in genes controlling patterning are driving phenotypic differences, even though mitochondrial loci were incompletely sorted (Palumbi et al 2001, Avise 2004.…”
Section: Geneticsmentioning
confidence: 99%
“…However, a series of studies on hamlets Hypoplectrus spp. found that even in the presence of assortative mating among many drastically different color forms, genetic struc turing is weak or almost completely absent (McCartney et al 2003, Ramon et al 2003, Puebla et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Strong genetic variability associated with both colour and sexual strategy have been found in different fishes (McCartney et al 2003). Among marine invertebrate species, studies of ascidians have pointed out discordant results.…”
Section: Population Genetic Analysesmentioning
confidence: 99%
“…Bierne et al 2003). Coral reef fish of the genus Hypoplectrus (hamlets), which have attracted increased attention in recent years (McCartney et al 2003, Ramon et al 2003, Puebla et al 2007, provide an ideal model for studying the speciation mechanisms of a polymorphic group with high geographic genetic connectivity within the expansive marine environment.…”
Section: Introductionmentioning
confidence: 99%
“…Hamlets show very strong assortative mating preferences for their own colour morph (Domeier 1994, Puebla et al 2007. Despite this fact, there are few clear genetic distinctions between morphs (McCartney et al 2003), which suggests recent morph diversification.…”
Section: Introductionmentioning
confidence: 99%